Reentrant Structural and Optical Properties and Large Positive Thermal Expansion in Perovskite Formamidinium Lead Iodide. Issue 49 (10th November 2016) - Fabini, Douglas H.; Stoumpos, Constantinos C.; Laurita, Geneva; Kaltzoglou, Andreas; Kontos, Athanassios G.; Falaras, Polycarpos; Kanatzidis, Mercouri G.; Seshadri, Ram
Abstract: The structure of the hybrid perovskite HC(NH2 )2 PbI3 (formamidinium lead iodide) reflects competing interactions associated with molecular motion, hydrogen bonding tendencies, thermally activated soft octahedral rotations, and the propensity for the Pb 2+ lone pair to express its stereochemistry. High‐resolution synchrotron X‐ray powder diffraction reveals a continuous transition from the cubic α‐phase (Pm 3 ‾ m, #221) to a tetragonal β‐phase (P4/mbm, #127) at around 285 K, followed by a first‐order transition to a tetragonal γ‐phase (retaining P4/mbm, #127) at 140 K. An unusual reentrant pseudosymmetry in the β‐to‐γ phase transition is seen that is also reflected in the photoluminescence. Around room temperature, the coefficient of volumetric thermal expansion is among the largest for any extended crystalline solid. Abstract : Extraordinary phase evolution : The hybrid perovskite formamidinium lead iodide undergoes two structural transitions in the 90 K to 490 K range. Deciphering these transitions points to unusually large thermal expansion in the tetragonal phases, and strong coupling between the reentrant lower temperature structural transition and the optical band gap.